2020
DOI: 10.3390/ijms21082723
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenic Origin of Micro RNAs in Atlantic Salmon (Salmo salar) Seminal Plasma

Abstract: The origin and contribution of seminal plasma RNAs into the whole semen RNA repertoire are poorly known, frequently being overlooked or neglected. In this study, we used high-throughput sequencing and RT-qPCR to profile microRNA (miRNA) constituents in the whole semen, as well as in fractionated spermatozoa and seminal plasma of Atlantic salmon (Salmo salar). We found 85 differentially accumulated miRNAs between spermatozoa and the seminal plasma. We identified a number of seminal plasma-enriched and spermatoz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…We further predicted the function of the differentially expressed miRNAs in the top 100 and found that these miRNAs (miR-143-3p, miR-152-3p, miR-378a-3p and miR-92a-3p) were related to cell cycle or meiosis. miR-143-3p [68], miR-152-3p [69], miR-378a-3p [70] and miR-92a-3p [71,72] have also been reported to be involved in the regulation of spermatogenesis or semen quality. It is interesting that there is no significant difference in the miRNAs (miR-20, miR-21 and miR-106a) involved in the self-renewal of spermatogonial stem cells [46], indicating that testicular heat stress under the conditions of this study has little effect on spermatogonial stem cells and they have good recovery ability after testicular heat stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…We further predicted the function of the differentially expressed miRNAs in the top 100 and found that these miRNAs (miR-143-3p, miR-152-3p, miR-378a-3p and miR-92a-3p) were related to cell cycle or meiosis. miR-143-3p [68], miR-152-3p [69], miR-378a-3p [70] and miR-92a-3p [71,72] have also been reported to be involved in the regulation of spermatogenesis or semen quality. It is interesting that there is no significant difference in the miRNAs (miR-20, miR-21 and miR-106a) involved in the self-renewal of spermatogonial stem cells [46], indicating that testicular heat stress under the conditions of this study has little effect on spermatogonial stem cells and they have good recovery ability after testicular heat stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the particular biological processes and related pathways in which these DE miRS are involved. The expression of miR-730a-5p was detected in the mature testis of Atlantic salmon [81], and was downregulated in the liver when genetically improved farmed tilapia (Oreochromis niloticus) was submitted to a heat stress (from 28 to 37.5 ‱ C [82]). It was found that miR-152-5p seems to act as a tumor suppressor in different sorts of cancers and/or controlling fibrosis progression [83][84][85].…”
Section: Circulating Non-coding Rnasmentioning
confidence: 99%
“…The miR-430 regulation of Cxcl12 chemokine signaling confers genetic robustness in directing PGC migration towards the genital ridge [ 38 ]. Another miRNA miR-202-5p has been reported as a gonad-specific miRNA in zebrafish [ 39 ], Atlantic salmon [ 40 ], and medaka [ 41 ]. In zebrafish, miR-202-5p is a component of maternal germ plasm [ 16 ].…”
Section: Introductionmentioning
confidence: 99%